The Influence of P3K Employee Status on the Independence, Loyalty, and Accountability of Government Apparatus - Safrida Safrida (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study explores the influence of Government Employee with Work Agreement (P3K) employment status on the independence, loyalty, and accountability of state apparatus in Indonesia. In the context of public reform administration, the presence of P3K personnel—who differ fundamentally from permanent civil servants (PNS) in terms of employment tenure, legal protection, and career development pathways—raises critical questions regarding their behavioral orientation and institutional commitment. This research aims to analyze whether the contractual nature of P3K employment affects the integrity of public service delivery, particularly in terms of the independence of decision-making, the depth of loyalty to the state and government institutions, and the degree of personal and institutional accountability. Using a mixed-methods approach, this study combines quantitative data from structured questionnaires distributed to P3K and PNS personnel across various government agencies with qualitative interviews involving supervisors and policy makers. The findings reveal that while P3K employees tend to demonstrate high task performance due to probationary pressures and evaluation-based renewals, there are measurable concerns about their independence, especially when faced with politically sensitive decisions. Loyalty patterns among P3K employees appear to be more transactional and career-driven compared to PNS, who show stronger affective and normative commitment. In terms of accountability, the contractual framework of P3K employment creates a paradox: while performance metrics are closely monitored, a sense of moral responsibility and long-term institutional attachment may be weak. This paper concludes that the integration of P3K personnel into the bureaucratic system necessitates a reconsideration of employment policy frameworks to balance efficiency, flexibility, and the core values ​​of public service. Strengthening institutional culture and ethical training may help mitigate the limitations associated with non-permanent employment status.